Added value? Denaturalizing the "good" of urban greening. Issue 8 (15th July 2019) - Angelo, Hillary
Abstract: In recent years, "urban greening" has become a new keyword in urban policy and practice, used to describe a proliferation of urban quality of life and environmental sustainability initiatives including street trees, public parks, greenways, farmers' markets, green roofs, and LEED certification in design. The emerging critical literature on urban greening has highlighted important ways green's social and economic added value affects the political economy of contemporary greening and produces inequalities in access to real or perceived environmental goods. However, such research has only infrequently asked why and under what conditions naturalized understandings of green as "good" make it possible for such initiatives to add value in the first place. As a result, it offers only partial explanations of why green has the effects it has—for instance, increasing property values—and only very rarely questions the fundamental "good" of nature itself. I argue that integrating insights on green's naturalized social and economic value from a growing body of social‐theoretical work across geography and the social sciences can complement political economic explanations for greening and provide new vantage points for critique.